Hydrology and morphology of two river mouth regions (temperate Vistula Delta and subtropical Red River Delta) - Zbigniew Pruszak; Pham Van Ninh; Marek Szmytkiewicz; Nguyen Manh Hung; Rafał Ostrowski (Oceanologia)
The paper presents a comparative analysis of two different river mouths from two different geographical zones (subtropical and temperate climatic regions). One is the multi-branch and multi-spit mouth of the Red River on the Gulf of Tonkin (Vietnam), the other is the smaller delta of the river Vistula on a bay of the Baltic Sea (Poland). The analysis focuses on the similarities and differences in the hydrodynamics between these estuaries and the adjacent coastal zones, the features of sediment transport, and the long-term morphodynamics of the river outlets. Salinity and water level are also discussed, the latter also in the context of the anticipated global effect of accelerated sea level rise. The analysis shows that the climatic and environmental conditions associated with geographical zones give rise to fundamental differences in the generation and dynamic evolution of the river mouths.